2019
DOI: 10.1097/brs.0000000000002900
|View full text |Cite
|
Sign up to set email alerts
|

Alert Timing and Corresponding Intervention With Intraoperative Spinal Cord Monitoring for High-Risk Spinal Surgery

Abstract: Study Design. Prospective multicenter study. Objective. To analyze the incidence of intraoperative spinal neuromonitoring (IONM) alerts and neurological complications, as well as to determine which interventions are most effective at preventing postoperative neurological complications following IONM alerts in high risk spinal surgeries. Summary of Background Data. IONM may play a role in identifying and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 27 publications
4
96
0
2
Order By: Relevance
“…Changes in somatosensory evoked potential (SEP) can signal impending spinal cord injuries, and Epstein et al [69] showed a reduction in neurologic deficits associated with SEP monitoring. Additionally, a recent multicenter analysis by Yoshida et al [77] found a rescue rate of 82.1% when IONM was used during surgical correction of cervical OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in somatosensory evoked potential (SEP) can signal impending spinal cord injuries, and Epstein et al [69] showed a reduction in neurologic deficits associated with SEP monitoring. Additionally, a recent multicenter analysis by Yoshida et al [77] found a rescue rate of 82.1% when IONM was used during surgical correction of cervical OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…After those series of interventions, the IOM signals partial recovery from the lowest point. Therefore, after the significant high-risk surgical points it was very necessary to continue observing the IOM signals for a few minutes, and appropriate timely interventions were very useful in restoring the signals [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Repeat bilateral loss of MEP signal was the result of inadequately addressing the spinal cord perfusion deficiencies prior to obtaining the desired correction. Yoshida et al, 8 in a prospective multicenter review, observed 57 alerts in 1009 deformity cases occurring with rod rotation (n ¼ 21), pedicle screw insertion (n ¼ 7), osteotomy closing (n ¼ 6), compression, distraction, cantilever, or translation (n ¼ 10), decompression (n ¼ 3), and root sacrifice (n ¼ 3). There were 6 other significant drops in signal that they state were unrelated to the surgery.…”
Section: Discussionmentioning
confidence: 99%